Perbahasan Potensi Jiwa Menurut Ibn Sina dan al-Ghazali: Discussion on the Potential of Soul According to Ibn Sina and al-Ghazali - Mohd Akib, Mohd Manawi; Syed Muhsin, Sharifah Basirah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
The concepts of psychology and soul receive a heated debate among early Muslim philosophers. Al-Kindi, al-Farabi, Ibn Sina, al-Ghazali and al-Razi were among the scholars that were engaged in the debate. Besides their discussion on the nature and inclination of the soul from the physical and spiritual view, the potential of the soul is also emphasized by them. From Islamic perspective, every human being needs to know the potential that exists in their soul so that they can utilize and take responsibility as a caliph in this world. Thus, this article highlights discussion on the potential of soul according to Ibn Sina and al-Ghazali based on their works. Among the issue highlighted on the potential of soul are the potential of plants, life and human.